CONTEXTUAL FEATURES PADA PENUGASAN BUKU TEKS MATEMATIKA MATERI KECEPATAN DAN DEBIT - Afifah Novi Hapsari; Fadhilatun Nurul Khasanah; Nur Rochimatul Muniroh (JIPD (Jurnal Inovasi Pendidikan Dasar), 2021)
Textbooks are one of the important tools in the world of education. Textbook lessons connect knowledge content in learning and used to determine how the learning process in the classroom. This study analyzes the text book “Senang Belajar Matematika” for grade V on the material about speed and discharge through contextual aspects of the situation/competence (contextual features) of the questions contained in it. The contextual feature’s categories are intra-mathematical context (C1), realistic context (C2), and authentic context (C3). The method used in this study is the method of content analysis in the textbooks in the study. Techniques and procedures of data analysis in this research is descriptive analysis technique. There are two analyzes used, namely horizontal and vertical analysis. The results showed that the book has a page size of 31.35 cm long and 22.65 cm wide with 266 pages. The contents of this book include 5 material items or chapters with approximately 10 kinds of activities in each chapter. Based on the Contextual Features analysis, it can be seen that of the 321 questions contained in the book “Senang Belajar Matematika” class V, the speed and discharge material is dominated by questions and assignments with the intra-mathematical category (C1) which has a total of 193 questions with a percentage of 60%, then the questions are categorized as realistic. (C2) as many as 120 with a percentage of 37%, and authentic category questions (C3) as many as 8 with a percentage of 3%.